Vegetable and Fruits Consumption, Physical Activity, and Nutritional Status of Adolescents - Nanda Rizkha Heratama; Kusnandar Kusnandar; Suminah Suminah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
The nutritional status of adolescents is one of the main challenges for health workers and the community. This study analyzed the relationship between vegetable consumption habits and physical activity with the nutritional status of adolescents. The research design used was cross-sectional. The sampling technique was carried out using the proportional random sampling method. The population in this study were teenagers in Pangkalpinang City. The sample consisted of 340 teenagers in the city of Pangkalpinang. The prevalence of malnutrition in adolescents is 38.2 with the prevalence of over and undernutrition being 31.2% and 7%, respectively. Most teenagers with good nutritional status (67.3%) have the habit of consuming vegetables frequently. The results of logistic regression analysis showed that the habit of consuming vegetables and physical activity had an effect on the nutritional status of adolescents. The risk of malnutrition increased significantly by 2.46 times in adolescents with less physical activity (p = 0.016) and increased by 1.94 times in adolescents with less vegetable consumption habits (p = 0.005). The community, especially adolescent families, needs to receive education about the importance of healthy habits such as the consumption of vegetables and fruit to maintain good nutritional status in adolescents.